Effects of the exopolysaccharide from Porphyridium cruentum coating on polyphenol oxidase activity and colour of fresh-cut banana during cold storage - Bertrand, Charlotte (2016)
Fresh-cut fruits are highly susceptible to enzymatic browning. The aim of this study was to evaluate the effects of the exopolysaccharide (EPS) from the marine microalga Porphyridium cruentum on polyphenol oxidase (PPO) activity and colour of ‘Cavendish’ banana slices during storage at 4°C. The banana slices became browner (L* values and/or chroma values decreased, and/or a* increased), while PPO activity of coated samples remained approximately constant throughout storage. EPS 5 g.L–1 solution could be used as a coating to prevent the browning of ‘Cavendish’ banana slices, although after six days of storage the results obtained on colour and PPO activity were very similar to those of carrageenan.